2006
DOI: 10.2151/jmsj.84.405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Greenhouse Warming on Tropical Cyclone Frequency

Abstract: Influences of sea surface temperature (SST) spatial patterns and cumulus parameterizations on tropical cyclone (TC) frequency, in the context of global warming impacts, are investigated using an atmospheric general circulation model at T106 horizontal resolution. Simulated TCs in this high-resolution model are categorized into tropical storms (TSs) and tropical depressions (TDs). Model TSs are defined as TCs with maximum surface wind speed more than, or equal to 16 m s À1 , for experiments with an Arakawa-Schu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
89
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 37 publications
14
89
0
Order By: Relevance
“…High-resolution downscaling simulations over the North Atlantic support this relative SST change hypothesis for TC frequency of occurrence (Knutson et al 2008). In these simulations, the SST threshold for TC genesis increases with tropical warming (see also Yoshimura et al 2006). Equipped with a detailed knowledge of tropical SST patterns, we discuss their influence on TC based on the TC potential intensity (PI) index of Emanuel (1986).…”
Section: Implications For Tropical Cyclone Changementioning
confidence: 81%
“…High-resolution downscaling simulations over the North Atlantic support this relative SST change hypothesis for TC frequency of occurrence (Knutson et al 2008). In these simulations, the SST threshold for TC genesis increases with tropical warming (see also Yoshimura et al 2006). Equipped with a detailed knowledge of tropical SST patterns, we discuss their influence on TC based on the TC potential intensity (PI) index of Emanuel (1986).…”
Section: Implications For Tropical Cyclone Changementioning
confidence: 81%
“…Most glaring is its dimensional inconsistency. Moreover, recent studies by Nolan et al (2007, hereafter N07) and Nolan and Rappin (2008, hereafter N08) showed that the index predicted an increase in genesis in an environment of increasing SST, whereas numerous GCM simulations with and without regional downscaling show a general decrease in genesis with increasing SST due to global warming (Sugi et al, 2002;Yoshimura et al, 2006;Bengtsson et al, 2007;Emanuel et al, 2008;Knutson et al, 2008), albeit with much regional variability.…”
Section: A Pseudo-indexmentioning
confidence: 99%
“…Recent studies (Sugi et al, 2002;Oouchi et al, 2006;Yoshimura et al, 2006;Bengtsson et al, 2007) have utilized GCMs to reproduce TC activity and to predict the level of TC activity in warmer climates. To improve upon the coarse resolution employed by GCMs, regional downscaling, in which a regional model is driven by GCM boundary conditions, has been applied to the problem (Knutson and Manabe, 1998;Knutson and Tuleya, 2004;Knutson et al, 2007Knutson et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…There is still an uncertainty about the future changes in tropical cyclone frequency and intensity [Oouchi et al, 2006;Yoshimura et al, 2006;Bengtsson et al, 2006]. Coarse resolution GCMs are not able to represent typical inner structures of tropical cyclones which results in underestimation of intensities [e.g., Krishnamurti et al, 1989;Camargo and Sobel, 2004].…”
Section: Predicted Future Changes In Cyclone Frequency and Intensitymentioning
confidence: 99%